Risk factors for anastomotic leakage after anterior resection for rectal cancer (RALAR study): A nationwide retrospective study of the Italian Society of Surgical Oncology Colorectal Cancer Network Collaborative Group. (6th December 2021) - Degiuli, Maurizio; Elmore, Ugo; De Luca, Raffaele; De Nardi, Paola; Tomatis, Mariano; Biondi, Alberto; Persiani, Roberto; Solaini, Leonardo; Rizzo, Gianluca; Soriero, Domenico; Cianflocca, Desiree; Milone, Marco; et al.
Abstract: Aim: Anastomotic leakage after restorative surgery for rectal cancer shows high morbidity and related mortality. Identification of risk factors could change operative planning, with indications for stoma construction. This retrospective multicentre study aims to assess the anastomotic leak rate, identify the independent risk factors and develop a clinical prediction model to calculate the probability of leakage. Methods: The study used data from 24 Italian referral centres of the Colorectal Cancer Network of the Italian Society of Surgical Oncology. Patients were classified into two groups, AL (anastomotic leak) or NoAL (no anastomotic leak). The effect of patient‐, disease‐, treatment‐ and postoperative outcome‐related factors on anastomotic leak after univariable and multivariable analysis was measured. Results: A total of 5398 patients were included, 552 in group AL and 4846 in group NoAL. The overall incidence of leaks was 10.2%, with a mean time interval of 6.8 days. The 30‐day leak‐related mortality was 2.6%. Sex, body mass index, tumour location, type of approach, number of cartridges employed, weight loss, clinical T stage and combined multiorgan resection were identified as independent risk factors. The stoma did not reduce the leak rate but significantly decreased leak severity and reoperation rate. A nomogram with a risk score (RALAR score) was developed to predict anastomotic leak risk at the end of resection. Conclusions: While a defunctioning stoma did not affect the leak risk, it significantly reduced its severity. Surgeons should recognize independent risk factors for leaks at the end of rectal resection and could calculate a risk score to select high‐risk patients eligible for protective stoma construction.